The TICAD aid network in the shadow of rising Asia-Africa partnerships - Raposo, Pedro Amakasu (2017)
As the first Asia-to-Africa development partnership to see daylight in 1993, the Tokyo International Conference on Africa Development (TICAD) has earned its place in Africa by creating an aid-network never seen before. Arguably, TICAD network produced opposed results: China and India launched similar partnerships with norms and aid practices against DAC norms of aid “tied” to trade and investment activities; represents a disruptive challenge to Japan’s model of partnership. Based on desktop study and structured interviews, it questions about the implications of TICAD normative principles for Africa for Asian development partnerships and for JICA in terms of ownership to understanding whether TICAD has changed them or instead was changed by them. It investigates how TICAD has influenced other emerging powers in Africa, who is “breaking” and why are not “taking” the DAC ODA norms, its implications towards aid effectiveness, the role of JICA and South-South Cooperation (SSC) in these development partnerships. This paper aims at finding points where TICAD normative principles can develop a differentiated view of inclusive and resilient SSC to increase TICAD development cooperation network. It finds that gradually Asian development partnerships differences (key principles and norms) are decreasing and their similarities (key areas and interests, cooperation modalities) are increasing.